2018
DOI: 10.1080/09513590.2018.1490403
|View full text |Cite
|
Sign up to set email alerts
|

Alternation of ten-eleven translocation 1, 2, and 3 expression in eutopic endometrium of women with endometriosis-associated infertility

Abstract: Little is known about the differences in ten-eleven translocation 1, 2, and 3 (TET1-3) expression in the endometrial phases in eutopic endometrium from infertile women with endometriosis (IWE) and fertile women without endometriosis (FW). Using RT-qPCR and western blot analysis, we assessed the TET expression in the mid-follicular and mid-luteal phases in eutopic endometrium from IWE (n = 38) and FW (n = 18). Both IWE and FW underwent laparoscopic and histological examinations for endometriosis. In the mid-lut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…There has been conflicting data on the expression and regulation of DNMTs in the endometrium, which implies the need for additional studies. As mentioned previously, studies by Ciesielski et al (), Roca et al (), and Szczepanska et al (), suggest the involvement of TETs in the onset of endometrial pathologies. However, these are the only three studies currently, that are indicative of a potential role of TETs in the endometrium and warrants further investigation on its role in endometriosis.…”
Section: Future Directionsmentioning
confidence: 55%
See 2 more Smart Citations
“…There has been conflicting data on the expression and regulation of DNMTs in the endometrium, which implies the need for additional studies. As mentioned previously, studies by Ciesielski et al (), Roca et al (), and Szczepanska et al (), suggest the involvement of TETs in the onset of endometrial pathologies. However, these are the only three studies currently, that are indicative of a potential role of TETs in the endometrium and warrants further investigation on its role in endometriosis.…”
Section: Future Directionsmentioning
confidence: 55%
“…This data in agreement with other studies, confirming an association between global 5hmC levels and TET expression (Ciesielski et al, ; Du et al, ; Murata et al, ; Putiri et al, ). Other recent studies looking at the involvement of TETs in endometriosis, reported TETs to be downregulated in an ectopic (Roca et al, ) and eutopic (Szczepańska et al, ) endometrial tissues. Despite having a lower TET gene expression, Roca et al () reported high global hydroxymethylation levels in the ectopic endometrium.…”
Section: Hydroxymethylation and Ten Eleven Translocation Proteinsmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the importance of demethylation processes and the involvement of TETs in endometrial changes during the menstrual cycle, and impaired expression of TETs in endometrial cancer were described [ 92 , 101 , 102 ]. The expression of TET1 and TET3 was higher in the mid-secretory phase than in the other phases of the endometrial cycle.…”
Section: Role Of Tet Enzymes In Uf Developmentmentioning
confidence: 99%
“…Despite this, the aetiology of the disorder is still elusive [3]. A growing body of scientific evidence has recently been linking endometriosis with an immunologic dysfunction, metabolic changes, the atherogenic lipid profile, oxidative stress as well as with chronic systemic inflammation [4,5].…”
Section: Introductionmentioning
confidence: 99%